The effect of interpreting experience on distance dynamics : Testing the literal translation hypothesis - Pavlović, Nataša (Array, 2013)
The aim of this process-oriented study is to test the literal translation hypothesis, i.e. the frequently held view that, in their search for the most suitable translation solution, translators move from more literal towards freer renderings. The study uses keystroke-logging to investigate translation processes involving self-revision in terms of ‘distance dynamics.’ The latter term refers to the fact that each new solution to a particular translation problem can be closer or more distant from the source item than the previous one. A more specific hypothesis is also tested, namely that experience in interpreting has an effect on distance dynamics. To this end, processes of two groups of subjects — translators without substantial interpreting experience, and interpreters — are compared. The findings challenge the literal translation hypothesis, and highlight some methodological issues that should be tackled in future studies.